Environmental Pollution Alerting System using IOT - T.Prem Jacob, Dr.; A.Pravin, Dr.; Albert Mayan, Mr. (International Journal of Engineering and Technology, 2018)
In metro cities the people living near a sewage treatment plant where there's a probability of harmful gas vaporous that may spread in atmosphere mostly at midnight which we should not breathe. For this reason, we have assembled a framework for detecting and cautioning the human being living nearby. The plan for the Environmental Alert System is an inspiration to avoid inhaling of various synthetic compounds noticeable all around. The unit comprises of a variety of four gas sensors each for methane, carbon monoxide, smoke, propane. We have developed with an Intel Edison for detecting wirelessly and cautioning. Environmental Alert System is a proper air pollution detecting gadget.Â Â